Pengaruh Faktor-Faktor Keuangan terhadap Kinerja Bank di Indonesia : Ulasan Literatur Semantik - Ahmad Firdaus; Deni Sunaryo; Calvin Wijaya Sung (Jurnal Visi Manajemen, 2024)
This study aims to conduct a semantic literature review related to the influence of financial factors such as Non-Performing Loans (NPL), bank size, corporate social responsibility (CSR), and adoption of electronic banking on bank performance in Indonesia. This study is relevant in providing an overview of how these factors affect bank performance and how they interact with each other in the context of the Indonesian banking sector. Method: A semantic-based literature review was conducted by identifying and categorizing relevant articles published between 2016 and 2023. The articles were analyzed based on keywords and phrases related to key topics such as NPL, bank size, CSR, and adoption of electronic banking. Literature data was selected from various reputable sources such as Google Scholar, Scopus, and JSTOR. Key Findings: This study found that NPL has a significant negative impact on bank profitability, while bank size can improve operational efficiency. CSR contributes to increasing public trust, which has an impact on financial performance. In addition, the adoption of e-banking has been shown to improve operational efficiency and consumer trust, which leads to improved bank financial performance. Contribution:This article contributes to the development of studies on bank financial performance in Indonesia, by linking internal and external factors that affect bank efficiency and profitability. This study also offers insights for policymakers and practitioners in formulating strategies to improve bank performance.